The "Big Bang" in obese fat: Events initiating obesity‐induced adipose tissue inflammation. Issue 9 (19th August 2015) - Wensveen, Felix M.; Valentić, Sonja; Šestan, Marko; Turk Wensveen, Tamara; Polić, Bojan
<x xml:space="preserve">Abstract</x> Obesity is associated with the accumulation of pro‐inflammatory cells in visceral adipose tissue (VAT), which is an important underlying cause of insulin resistance and progression to diabetes mellitus type 2 (DM2). Although the role of pro‐inflammatory cytokines in disease development is established, the initiating events leading to immune cell activation remain elusive. Lean adipose tissue is predominantly populated with regulatory cells, such as eosinophils and type 2 innate lymphocytes. These cells maintain tissue homeostasis through the excretion of type 2 cytokines, such as IL‐4, IL‐5, and IL‐13, which keep adipose tissue macrophages (ATMs) in an anti‐inflammatory, M2‐like state. Diet‐induced obesity is associated with the loss of tissue homeostasis and development of type 1 inflammatory responses in VAT, characterized by IFN‐γ. A key event is a shift of ATMs toward an M1 phenotype. Recent studies show that obesity‐induced adipocyte hypertrophy results in upregulated surface expression of stress markers. Adipose stress is detected by local sentinels, such as NK cells and CD8+ T cells, which produce IFN‐γ, driving M1 ATM polarization. A rapid accumulation of pro‐inflammatory cells in VAT follows, leading to inflammation. In this review, we provide an overview of events leading to adipose tissue inflammation, with a special focus on adipose homeostasis and the obesity‐induced loss of homeostasis which marks the initiation of VAT inflammation.